"Inflamm‐aging" influences immune cell survival factors in human bone marrow. Issue 3 (11th January 2017) - Pangrazzi, Luca; Meryk, Andreas; Naismith, Erin; Koziel, Rafal; Lair, Julian; Krismer, Martin; Trieb, Klemens; Grubeck‐Loebenstein, Beatrix
Abstract : Immune responses in the human bone marrow in old age: Senescent cells secrete inflammatory mediators and high amounts of ROS. These factors trigger CD11c hi+, CD14 +, and CD34 + cells to produce IL‐6 and IL‐15 in the bone marrow. Both cytokines are important for the survival of highly differentiated CD8 + CD28 ‐ T cells, which produce IFNγ and TNF, thus perpetuating the "inflammaging" cycle. CD8 + CD28 ‐ T cells may compete for space with CD4 + memory cells and long‐lived plasma cells. Abstract : The bone marrow (BM) plays a key role in the long‐term maintenance of immunological memory. However, the impact of aging on the production of survival factors for effector/memory T cells and plasma cells in the human BM has not been studied. We now show that the expression of molecules involved in the maintenance of immunological memory in the human BM changes with age. While IL‐15, which protects potentially harmful CD8 + CD28 − senescent T cells, increases, IL‐7 decreases. IL‐6, which may synergize with IL‐15, is also overexpressed. In contrast, a proliferation‐inducing ligand, a plasma cell survival factor, is reduced. IFN‐y, TNF, and ROS accumulate in the BM in old age. IL‐15 and IL‐6 expression are stimulated by IFN‐y and correlate with ROS levels in BM mononuclear cells. Both cytokines are reduced by incubation with the ROS scavengers N‐acetylcysteine and vitamin C. IL‐15 and IL‐6 are also overexpressed in the BM of superoxide dismutase 1 knockout mice compared to their WT counterparts. In summary, our results demonstrate the role of inflammation and oxidative stress in age‐related changes of immune cell survival factors in the BM, suggesting that antioxidants may be beneficial in counteracting immunosenescence by improving immunological memory in old age.